The middle-class entrepreneurial elite in Šibenik and Split : (15th century) - Andrić, Tonija (Array, 2019)
The paper explores the entrepreneurial elite of late medieval Šibenik and Split, based on the examples of prominent businessmen in the historical records preserved in the notarial records of the two cities.